No effect of an oleoylethanolamide-related phospholipid on satiety and energy intake: a randomised controlled trial of phosphatidylethanolamine - LITHANDER, FIONA (BioMed Central, 2008)
Phosphatidylethanolamine (PE) is a phospholipid which is biosynthesized into long chain N-acylethanolamines (NAEs) including oleoylethanolamide (OEA), a known inhibitor of food intake. The aim of this study was to investigate whether PE-containing lipids can also inhibit intake. This was a 4 treatment intervention where 18 male participants were given a high-fat test breakfast (2.5 MJ, 53 en% fat) containing (i) high-phospholipid, high-PE lipid (ii) high-phospholipid, medium-PE lipid (iii) no-phospholipid, no-PE control lipid or (iv) water control, in a randomised cross-over. Visual analogue scales (VAS) were used to assess post-ingestive hunger and satiety, and energy intake (EI) was measured at an ad libitum lunch meal after 3.5 hours. RESULTS: When compared with the water control, the 3 lipid treatments resulted in lower levels of hunger and thoughts of food, greater fullness and satisfaction (all, treatment*time interaction, P<0.001), and a lower EI (P<0.05). However, there was no difference in any of the VAS measures when the 2 PE lipid treatments were compared with no-PE control lipid, nor when medium-PE was compared with high-PE. Unexpectedly participants ate significantly more energy at the lunch meal when the 2 PE lipid treatments (medium-PE:5406 kJ, 334 sem; high-PE:5288 kJ, 244 sem) were compared with the no-PE control lipid (5072 kJ, 262 sem, P<0.05), although there was no dose effect between the medium- and high-PE treatments. CONCLUSION: Despite the close relationship of PE with OEA, there was no evidence from this acute study that dietary phospholipids containing PE can favourably modify eating behaviour.
PUBLISHED
Keywords: FEL protocol supervision, patient recruitment, registration, data collection, data entry, co-senior author. CMS data collection, data entry, manuscript preparation. ATM physician, clinical oversight of the participants, manuscript preparation. AKM development and preparation of the PE product. BHM biostatistician. SDP fundraiser, protocol design, study oversight